Welfare and competition effects of electricity interconnection between Great Britan and Ireland - Laura Malaguzzi Valeri (The Economic and Social Research Institute (ESRI), 2008)
This study analyzes the effects of additional interconnection on welfare and competition in the Irish electricity market. I simulate the wholesale electricity markets of Great Britain and the island of Ireland for 2005. I find that in order for the two markets to be integrated in 2005, additional interconnection would have to be large. The amount of interconnection decreases for high costs of carbon, since this causes the markets to become more similar. Irish consumers obtain most of the welfare gains of interconnection. As the amount of interconnection increases, there are also positive effects on competition in Ireland, the less competitive of the two markets. Finally, it is unlikely that private investors will pay for the construction of the interconnector since they are unable to extract all its welfare benefits.
Keywords: L94; Q40; 330; interconnection; electricity; Ireland; Elektrizitätswirtschaft; Stromnetz; Energieverbund; Wohlfahrtseffekt; Internationaler Wettbewerb; Großbritannien; Irland